The incidence and determinants of employee involvement: Evidence from the Finnish manufacturing sector - Derek C. Jones; Panu Kalmi; Takao Kato; Mikko Mäkinen (The Research Institute of the Finnish Economy (ETLA), 2008)
In this paper, we present preliminary empirical findings on the incidence of employee involvement practices in the Finnish manufacturing sector. The novel survey on EI practices is based on a representative random sample from the population of the Finnish manufacturing firms who had 50 or more employees in 2005. Our main findings are that employee involvement practices are widespread in Finnish firms, although there is variation in the use of individual practices. Job rotation and satisfaction surveys are the most common practices and board representation the least common. Studying the determinants of these practices, we find evidence that they are more commonly used in larger firms and in firms that use heavily other advanced management practices.
Keywords: M54; J41; J53; C21; 330; new workplace practices; HRM; employee participation; Personalmanagement; Mitbestimmung; Arbeitsorganisation; Verarbeitendes Gewerbe; Finnland